"NeckarPark Stuttgart": District heat from wastewater. (September 2018) - Erhorn, H.; Görres, J.; Illner, M.; Bruhn, J.-P.; Bergmann, A.
Abstract: The 22-hectare area of the former freight station is currently Stuttgart's largest urban development project. In addition to commercial and service areas, around 850 residential units are to be built on a net floor area totaling 220, 000 m². The energy concept includes heat recovery from wastewater with a capacity of 2.1 megawatts, which is extracted from a nearby sewer. The energy concept is supplemented by cogeneration units. In the NeckarPark district a low-temperature four-pipe heating grid, which is built by the state capital Stuttgart and operated by the city-owned energy supplier (Stadtwerke Stuttgart), provides heat to the buildings.